Hate Speech Analysis in Documentary Film “Ice Cold: Murder, Coffee and Jessica Wongso” - Adib Kurnaiwan; Tiara Nanda Dewi; Febri Wijayanti (Universitas Negeri Malang, 2024)
Hate speeches is a form of discrimination that can have a negative impact on victims . With the increasingly rapid development of technology , the media and the internet are often used as tools to carry out hate speech , one of which is represented in films . Several previous studies have shown that hate speeches through the media can harm society and strengthen negative stereotypes against certain groups . Most of the hate speeches comes from the language used . This research aims to analyze the frequency level of forms of verbal hate speech in the documentary film